STUDY OF THE ENVIRONMENTAL CHARACTERS ON GERMINATION PROPERTIES OF SEEDS OF THYMUS DAENENSIS AND T.VULGARIS - yadegari, mehrab (Journal of Agricultural Sciences (Belgrade), 2019)
This research conducted to investigate whether of salinity, temperature, light, pH and seeding depth on germination characters of two species of Thyme at 2017. Two in vitro experiments with four replications by randomized complete design were conducted in laboratory condition. Treatments contained: a)Fluctuating temperature in germinator 5/15, 10/20, 15/25, 15/30 and 20/35 centigrade night/day, b) Concentrations of salinity by using solutions of 0, 10, 20, 40, 80, 160 and 320 mM NaCl C) Seeding depth contained of 0, 1.5, 3 and 6cm, pH included: 5, 6, 7, 8, 9. Results showed that the effect of different treatments on percentage, speed and vigour of seeds of Thyme were significant. Almost upper amounts of treatments, had negative effectiveness on germination characters. Emergence decreased with increased concentration of salinity, planting depth and pH. In two species, the most of germination percentage (94%) obtained in treatment combination of 15/25 (day/night), 0mM of NaCl, 1Cm 0f planting depth and pH=7. Germination was stopped in combination of treatments of 35/20 (day / night), 320mM of NaCl, 6Cm 0f planting depth and pH=9. Each of treatments in upper level, had intercepter effect but effects in combination with higher level of another treatments, had more destructive.